Turnover Intention Among Generation Z Employees: A Systematic Review - Indra Taruna Anggapradja; Darwis Agustriyana; Vina Silviani Marinda (Maneggio, 2026)
Employee turnover intention remains a critical organizational issue, particularly among Generation Z employees who are entering the workforce and exhibiting high early-career mobility. Despite extensive turnover research, empirical findings on Generation Z remain conceptually fragmented and insufficiently consolidated. This study aims to systematically review empirical research on turnover intention among Generation Z employees and identify the dominant determinants influencing their intention to leave. A systematic literature review (SLR) approach was adopted, drawing on Scopus and Web of Science databases within the 2019–2025 publication timeframe. Following a structured screening process, 20 peer-reviewed empirical studies were included in the final synthesis. The findings indicate that organizational-level factors—particularly perceived organizational support, leadership quality, and career development opportunities—are the most consistent predictors of turnover intention. However, these determinants largely operate indirectly through psychological mediators, including job satisfaction, affective commitment, work engagement, psychological capital, and job embeddedness. Affective commitment emerged as the most robust explanatory mechanism across diverse national contexts, suggesting that Generation Z retention decisions are fundamentally relational and emotionally anchored rather than purely transactional. The study contributes by consolidating dispersed evidence into an integrated framework and offers practical guidance for organizations to prioritize relational leadership, developmental HR practices, and psychologically supportive environments to enhance retention among Generation Z employees.